Speedy Response Is Needed - Vallejo Times-Herald (Vallejo Times-Herald)
There is very little time remaining to organize and conduct a campaign to fill Friend Ship Golden Bear with food and clothing for stricken France, Italy and Greece. If we desire to give the City of Vallejo and the County of Solano a spot in the picture by providing a sizeable quantity of the needed materials for the first loading, our actions must be spontaneous and liberal. There will be little time for solicitation or for arousing public interest by publicizing the human need or the benefits that will accrue from our gifts.